MOSQUITOES OF THE BOGOR BOTANICAL GARDENS - SOENARTONO ADISOEMARTO (BERITA BIOLOGI, 1977)
Various types of plant communities in boanical gardens provide surroundings for animal ife.In addition to their main role in botany,he botanical gardens provide aspects for zoological investigations as well(Adisoemarto 1974) The Bogor Botanical Gardens provide most of all possible types of environments for the development and construction of mosquito population.To develop the study of some ecological aspects of the mosquitoes, the availability of qualitative data is very much desired. For this purpose, observations on mosquito fauna have been carried out in the Bogor Botanical Gardens and the Results are presented in this paper.